Perspectives of using virtual educational platform MOODLE in the process of studying the course Information Literacy (Confluenţe Bibliologice, 2017)
The paper deals with the problems of applying electronic resources on the MOODLE platform for Information Literacy distance course.. The structure of the course and the opportunities of the MOODLE learning platform are represented.
Keywords: Information Literacy; MOODLE; distance learning